Performance evaluation of biodiesel from used domestic waste oils: a review - Diya'uddeen, B.H.; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan; Chakrabarti, M.H. (2012)
Global warming, high-energy demand and availability of new technologies are among the factors catalyzing the search for alternative sources of energy. Currently, there is renewed interest in obtaining energy from wastes hitherto meant for disposal. Increased costs of disposal and their attendant problems of heavy environmental loading are some aspects making the disposal option unattractive. These wastes are sources of energy and among the several sources of generating this energy are the waste-to-energy (WTE) categories with potentials for useable fuel production. The WTE materials are mainly used domestic waste oils (UDWOs), municipal solid waste (MSW), agricultural and industrial wastes. However, the latter wastes are not attractive as they consist of innumerable hazardous contaminants. The UDWOs are arguably a safe and cost effective source of useable fuel. Their conversion offers the merits of a reduction in greenhouse gas emission (GHG), enhancing fuel diversification and a qualitatively comparable energy output to fossil diesel fuels. Thus, UDWOs could significantly contribute towards achieving the 2020 and 2030 goals of substituting approximately 20 and 30 of petro-diesel with biofuels in US and EU, respectively. Moreover, attaining the forecasted annual production rate of 227 billion liters of biofuel by most active stakeholders in the biodiesel industry could be easily achieved. This review aims to analyze the performance of biodiesel fuels obtained from UDWO and to demonstrate the suitability of applying these fuels as substitutes to mineral diesel in various industries. Benefits of UDWO as a biodiesel feedstock were as well highlighted. Â© 2012 The Institution of Chemical Engineers.